Salivary urea and uric acid levels as biomarkers in dental caries: in vivo study - Raj, Gagan; Kumar, Dhananjaya; B. S., Suma; Mangal, Garima (International Journal Of Community Medicine And Public Health, 2022)
Background: A new approach in caries research is focused on the fact that salivary Substrates, like urea and uric acid, may play an important role in biofilm pH, homeostasis and in inhibiting dental caries and thus act as biomarker. Methods: A clinical in vivo study was conducted in Dental college of Patna among simple random sample of 30 dental students (10 caries active and 20 caries free based on DMFT index) and of age group 18-25 years after satisfying the inclusion and exclusion criteria. Unstimulated saliva samples of dental students were collected at Coachman position using draining technique and salivary urea and uric acid estimation done at private pathology laboratory, Patna. Results: The mean for urea level was higher among Caries free Group (61.15±18.85) as compared to Caries group (9.91±3.64) while the mean uric acid level was higher among Caries group (10.19±2.16) as compared to caries free group (5.25±2.78). The caries experience when assessed by correlating the DMFT Score with salivary urea and salivary uric acid concentration, it was found that the DMFT Score is in negative correlation with urea level (r=-0.790) and positive correlation with uric acid level (r=0.751) suggesting when salivary urea level increases there was decrease in caries rate and vice versa. Conclusions: Thus value of salivary urea and uric acid in adolescence can serve as a parameter for determining the risk of caries, thus acting as biomarkers in dental caries and this, in turn, can be used in the planning and implementation of appropriate caries preventive measures.